2023
DOI: 10.1111/1541-4337.13140
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of phthalates in different food matrices: A systematic review of the main sources of contamination and potential risks

Abstract: This systematic review aimed to investigate the occurrence of phthalates (phthalic acid esters [PAEs]) in different food matrices, as well as report the main sources of PAEs in food, the potential risks to the population, and the factors that influence its migration from food contact materials (FCMs) to food. Nineteen PAEs were identified, including di‐(2‐ehtylhexyl) phthalate (DEHP), dibutyl‐phthalate (DBP), benzylbutyl phthalate (BBP), diisononyl phthalate (DINP), and diisodecyl phthalate (DIDP) in fruits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 62 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…The regulations on the restrictions on the use of phthalates are different between international legislations; moreover, they consider only phthalates with high rates of application, and thus, high risk of exposure, which are listed as toxic, for example, di-methyl phthalate (DMP), benzyl butylphthalate (BBzP), DEHP, DnBP, di-iso-nonyl phthalate (DiNP), di-isodecyl phthalate (DiDP), and di-n-octyl phthalate (DnOP). The restrictions mainly concern food contacts materials (FCM), cosmetics, toys, and childcare articles [2,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The regulations on the restrictions on the use of phthalates are different between international legislations; moreover, they consider only phthalates with high rates of application, and thus, high risk of exposure, which are listed as toxic, for example, di-methyl phthalate (DMP), benzyl butylphthalate (BBzP), DEHP, DnBP, di-iso-nonyl phthalate (DiNP), di-isodecyl phthalate (DiDP), and di-n-octyl phthalate (DnOP). The restrictions mainly concern food contacts materials (FCM), cosmetics, toys, and childcare articles [2,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in the cheese samples included in our study, as different phthalate esters were detected. In more detail, a systematic review by da Costa et al 22 concluded that dairy products were listed among foods with the highest content in DEHP and DBP. These authors also confirmed the legal limits of these phthalates were exceeded, representing a potential risk exposure for both adults and children 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, a systematic review by da Costa et al 22 concluded that dairy products were listed among foods with the highest content in DEHP and DBP. These authors also confirmed the legal limits of these phthalates were exceeded, representing a potential risk exposure for both adults and children 22 . Similar results were obtained in our study where the average content of DEHP and DBP was highly detected.…”
Section: Discussionmentioning
confidence: 99%